Social perception on the integration of children with special educational needs in mainstream education - Șiangă, Zoia; Sandu, Mihaela Luminița (Eximia, 2024)
The inclusion of students with Special Educational Needs (SEN) within the general education system is a complex and persistent issue, considering that although educational policies and national legislation affirm support for the principle of inclusion, it is often implemented only at a declarative level. In the theoretical part, the evolution and progress of inclusive education at the international level was addressed, emphasizing the significant contribution of the United Nations Organization and various international conferences in promoting the individual rights of people with special needs. Another aspect considered the integration of students with special educational needs into the mainstream educational system, highlighting the crucial role and support offered to them. It is also emphasized the importance of the continuous professional development of teachers and the active involvement of parents in the educational process, as central pillars in the promotion of effective inclusive education. The methodology applied in the study regarding the integration of students with SEN in the Romanian educational system has as its main objectives the identification and analysis of teachers' perceptions and attitudes towards the integration process, the differences found between teaching staff from urban and rural environments, as well as examining the correlation between teachers' optimism and their perspectives on inclusion. Another important goal of the research is to identify barriers to the effective implementation of current and future public policies related to inclusive education. The research instruments used include an original questionnaire, entitled „Teachers' Beliefs and Attitudes about the Integration of Students with SEN”, intended to assess teachers' perceptions of inclusion, and an optimism measuring instrument, composed of 48 items, used to assess the level of optimism of the respondents. The sample of the study was made up of 60 teaching staff, aged between 25 and 45, divided into two groups, depending on the environment of origin (rural/urban). The analysis of the collected data indicates a greater predisposition towards acceptance and positive attitudes towards inclusion on the part of teachers from the urban environment, compared to their counterparts from the rural environment. Also, the results emphasize the existence of a positive correlation between the level of teachers' optimism and their attitude towards the inclusion of students with SEN. In conclusion, the findings of this research emphasize the significance of increasing the professionalism of teachers in supporting inclusive education and reveal notable disparities between rural and urban teachers in terms of the integration of students with special educational needs.